Markov dynamics on the cone of discrete Radon measures - Finkelshtein, Dmitri; Kondratiev, Yuri; Kuchling, Peter (Methods of functional analysis and typology)
We start with a brief overview of the known facts about the spaces of discrete Radon measures those may be considered as generalizations of configuration spaces. Then we study three Markov dynamics on the spaces of discrete Radon measures: analogues of the contact model, of the Bolker--Dieckmann--Law--Pacala model, and of the Glauber-type dynamics. We show how the results obtained previously for the configuration spaces can be modified for the case of the spaces of discrete Radon measures.